TINGKAT KEPUASAN PELANGGAN PADA GIANT EKSTRA PANAM PEKANBARU - Silvia, Adilla; Syahza, Almasdi; Syabrus, Hardisem (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research was for analyzing the satisfaction of customer at Giant Ekstra in Panam, Pekanbaru. The population of this research were all customers who shopping at Giant Ekstra. The sample that used in this research were 100 respondents. For analyzing the data using Important Performance Analysis (IPA) to seen how far the customer feel satisfied .That have been seen from the result of testing the level of members satisfaction used the method of Importance Performance Analysis (IPA) there were five attributes included in A quadrant (Top Priority), which was means considered important by members but didn’t maximized nor satisfied. And the range of the all factors result which was equal to 78,64%.Key words: Customer Satisfaction, Importance Performance Analysis (IPA).